Dermal Exposure Associated With Occupational End Use of Pesticides and the Role of Protective Measures - MacFarlane, E.; Carey, R.; Keegel, T.; El-Zaemey, S.; Fritschi, Lin (Occupational Safety and Health Research Institute, 2013)
Background: Occupational end users of pesticides may experience bodily absorption of the pesticideproducts they use, risking possible health effects. The purpose of this paper is to provide a guide forresearchers, practitioners, and policy makers working in the field of agricultural health or other areaswhere occupational end use of pesticides and exposure issues are of interest.Methods: This paper characterizes the health effects of pesticide exposure, jobs associated with pesticide use, pesticide-related tasks, absorption of pesticides through the skin, and the use of personal protective equipment (PPE) for reducing exposure.Conclusions: Although international and national efforts to reduce pesticide exposure through regulatorymeans should continue, it is difficult in the agricultural sector to implement engineering or systemcontrols. It is clear that use of PPE does reduce dermal pesticide exposure but compliance among themajority of occupationally exposed pesticide end users appears to be poor. More research is needed onhigher-order controls to reduce pesticide exposure and to understand the reasons for poor compliancewith PPE and identify effective training methods.